Effect of Age of Rootstock on Success of Bud Grafting jn Wood Apple (Feronia limonia (L.) Swingle) - Kadam, j H; Karale, A R; Desai, U T; Chandan, P M; Kamble, A B (Annals of Arid Zone, 2016)
Short Communication